Effect of organic seed treatment and foliar spray on growth, yield and resultant seed quality in sesame (Sesamum indicum L.): ORGANIC SEED TREATMENT ON SESAME YIELD - M PRAKASH; G SATHIYA NARAYANAN; R ANANDAN; B SUNIL KUMAR (Journal of Oilseeds Research, 2019)
Sesame (Sesamum indicum L.) is one of the ancient and most important oilseed crops and its seeds, contain around 50 per cent oil and 25 per cent protein. It is sixth most important oil seed crop in India and has great economic potential due to the possibilities for its exploitation in both the domestic and international markets. The usage of organic inputs is gaining importance nowadays in the context of environmental sustainability. Field experiments were carried out to study the effect of leaf extracts of four plants on seed yield of sesame under rainfed conditions. The seeds ofsesame cv. TMV 3 were treated with leaf extracts of pungam (Pongmia pinnata), prosopis (Prosopis juliflora), arappu (Albizia amara) and moringa (Moringa oleifera) @ 5% along with foliar spray @10 % at vegetative and flowering stages under rainfed condition along with water sprayed control. The results revealed that pre sowing seed treatment with moringa leaf extract @ 5% + foliar spray of moringa leaf extract @ 10 % at vegetative and flowering stages recorded higher seed yield and better seed quality when compared to other treatments and control.